PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN MENGINAP DI HOTEL INDONESIA KEMPINSKI JAKARTA - Skolastika Fenny Febrianti; Rivera Pantro Sukma Silitonga (Human Capital Development, 2023)
The purpose of this study was to determine the effect of service quality and promotion on customer satisfaction through the decision to stay at the Indonesia Kempinski Jakarta hotel. The data analysis method in this study used SmartPLS 3 software. The sampling used was purposive sampling with a sample of 200 respondents. The results showed that there was a positive and significant direct effect, namely service quality on customer satisfaction, service quality on the decision to stay, promotion on customer satisfaction, and promotion on the decision to stay. For the indirect effect, namely service quality has a significant effect on customer satisfaction through the decision to stay and promotion has a significant effect on customer satisfaction through the decision to stay.